Rasgos que identifican a algunos Vertisoles de la Zona Central de Chile - Luzio L., Walter; Menis M., Monica (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Physical, physico-chemical, mineralogical, macro-and micromorphological characterisitics of clay soils from the Central Zone of Chile were studied. It was concluded that the incipient degree of soil evolution is characterized by the presence of high quantities of weatherable minerals, the Quella Soil Series, with and without carbonates, being the youngest ones. Micromorphology demonstrated the presence of different kinds illuviation cutans, mainly normal void ferriargillans in the deep horizons, a situation wich along with granulometric distribution and physicochemical analysis suggests the existence of horizons of material accumulation at least in two of the four soil series. Finally, intergrade between Vertisols and other Soil Orders having accumulation horizons are proposed